Socialization of the Harmony Counseling Model as an Effort to Develop Counselor Professionalism - Nanda Alfan Kurniawan; Nur Hidayah; Sa’dun Akbar; M. Ramli; Husni Hanafi; Destanika Dhiffa Ralianti (Indonesia Berdaya, 2026)
This community service activity aimed to strengthen the competence of school counselors in Malang Regency through the socialization of the Harmoni Counseling Model. The model was developed to enhance students’ career decision-making skills using a contextual approach that integrates cognitive, affective, and conative dimensions. Its novelty lies in the application of life-value-based principles to support counselor professionalism in addressing student challenges in the era of disruption. The implementation involved needs assessment, material design, focus group discussions, practical simulations, and participant reflection. Eleven vocational school counselors participated, selected purposively through the regional counseling teachers’ association. Evaluation was conducted through questionnaires and observations, analyzed using Aiken’s V to assess understanding levels. The results indicated strong engagement, with 90.9 percent of participants showing enthusiasm for the model’s application. The analysis revealed high validity (≥0.83) across six understanding aspects, with two aspects achieving a perfect score of 1.00. Counselors demonstrated comprehensive understanding of the model’s rationale, objectives, and implementation guidelines, though the concept of student career development tasks required refinement. Overall, the program effectively enhanced counselor competence and confirmed the Harmoni Counseling Model’s relevance as a research-based approach for professional development and sustainable counseling practice.